Electric Polarization in Magnetic Topological Nodal Semimetal Thin Films - Yuya Ominato; Ai Yamakage; Kentaro Nomura (Condensed Matter, 2018)
We theoretically study the electric polarization in magnetic topological nodal semimetal thin films. In magnetically doped topological insulators, topological nodal semimetal phases emerge once the exchange coupling overcomes the band gap. Changing the magnetization direction, nodal structure is modulated and the system becomes topological nodal point or line semimetals. We find that nodal line semimetals are characterized by non-linear electric polarization, which is not observed in nodal point semimetals. The non-linear response originates from the existence of the surface states. Screening effect is self consistently included within a mean field approximation and the non-linear electric polarization is observed even in the presence of screening effect.